Partial purification and characterization of polyphenol oxidase and peroxidase from chestnut kernel. Issue 2 (March 2015) - Gong, Zhiqing; Li, Dajing; Liu, Chunquan; Cheng, Anwei; Wang, Wenliang
Abstract: Presently there is very little information about the properties of polyphenol oxidase (PPO) and peroxidase (POD) from chestnut, which are both related with chestnut browning. The chestnut PPO and POD were partially purified by acetone extraction, 30–80 g/100 mL ammonium sulfate fractionation, DE-52 anion-exchange column. PPO and POD activity increased 4.6-fold and 9.52-fold, its yields were 2.03 U/100 U and 4.21 U/100 U, and its specific activity was 1375 and 16, 500 U mg −1 protein after DE-52. SDS-PAGE results indicated that the molecular mass of PPO and POD was approximately 32.5 and 30.3 kDa, respectively. Its optima pH value for catalyzing catechol and 2-hydroxy phenol was both 7.0. The optimum temperature of PPO and POD for catalyzing catechol and 2-hydroxy phenol was found to be 40 and 50 °C, respectively. PPO showed the highest affinity to catechol among all our selected substrates. The K m and V max of PPO for substrate catechol were 92 mmol/L and 1.53 △OD/min. The K m and V max of POD for substrate 2-hydroxy phenol were 49 mmol/L and 0.2373 △OD/min. The investigation on the properties of PPO and POD is greatly important for minimizing the losses caused by fruit browning during chestnut processing. Highlights: Properties of partially purified chestnut POD after DE-52 anion-exchange column, were analyzed. Chestnut PPO and POD was co-eluted during ion exchange enzyme profile. Molecular mass of PPO and POD estimated by SDS-PAGE, was almost same.